Cognitive Processes in Language - Badio, Janusz; Badio, Janusz; Kosecki, Krzysztof (Peter Lang, 2014)
This book contains discussions of a broad range of issues of the relation between language and cognition, inspired mainly by recent developments in Cognitive Linguistics. The individual texts discuss, from various perspectives, conceptual strategies, verbal memory, syntax, semantics, linguistic segmentation, non-verbal communication, linguistic categorization, language learning, speech disorders, as well as applications of Cognitive Linguistics to the study of literature. The volume is a fresh contribution to the growing body of research in Cognitive Linguistics and the study of various cognitive processes in language.